2018
DOI: 10.1186/s12944-018-0874-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score (GRS) constructed from polymorphisms in the PON1, IL-6, ITGB3, and ALDH2 genes is associated with the risk of coronary artery disease in Pakistani subjects

Abstract: BackgroundCoronary artery disease (CAD) is a major killer in today’s world. Pakistan is also affected by this non-communicable disease like other countries. It is a multifactorial disease and is influenced by many gene-gene and gene-environment interactions.MethodsA total of 623 (219 controls, 404 cases) Pakistani subjects were genotyped for four SNPs, rs662 (PON1), rs5918 (ITGB3), rs671 (ALDH2), rs1800795 (IL-6) by PCR-RFLP. Various anthropometric parameters were noted and serum lipid profile was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Cardiovascular diseases are known to be a top cause of human mortality worldwide. Studies have shown that cardiovascular disorders are more likely to cause death in the general population than other diseases such as infectious diseases, maternal and infant diseases, nutritional disorders, and cancers [1][2][3][4]. The mortality rate from cardiovascular diseases is reported to be 45% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases are known to be a top cause of human mortality worldwide. Studies have shown that cardiovascular disorders are more likely to cause death in the general population than other diseases such as infectious diseases, maternal and infant diseases, nutritional disorders, and cancers [1][2][3][4]. The mortality rate from cardiovascular diseases is reported to be 45% [5].…”
Section: Introductionmentioning
confidence: 99%
“…GRS is a summation of genotypic scores of disease-associated variants combining the genetic effects of multiple causal variants [23] . It is currently widely used in various diseases, and single nucleotide polymorphism (SNP) is often used as a genetic susceptibility factor for risk assessment [ 24 , 25 ]. In order to correspond to the machine learning model, in addition to SNPs, we also included the pathogenic sites as genetic susceptibility factors in our study.…”
Section: Methodsmentioning
confidence: 99%
“…For each individual SNP, no statistically significant associations with CHD were found, in contrast to the GRS constructed from them ( p = 1.4 × 10 −4 ). Nevertheless, those authors note that a panel of SNPs included in a GRS should be designed carefully, in particular, the predisposition to the disease in different ethnic groups should be taken into consideration [ 76 ].…”
Section: Modern Models Of Genetic Risk Calculators (2016–2020)mentioning
confidence: 99%